Characterization system and method for solid-state battery atomic scale sample preparation completely isolated from air and application of characterization system and method
Through the samples and characteristics of a all -solid -state battery in the environmental or liquid nitrogen environment, the difficulty of samples and representation caused by the sensitivity of the battery air, the interface interface of the atomic scale of the all -solid battery, reveals the electrode materials and electrolytes The impact of micro -structure on macro performance.
Patent Information
- Application Number
- CN202411529105.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-24
AI Technical Summary
The air stability and electron beam/ion beam sensitivity of all-solid state batteries lead to insufficient sample preparation and characterization methods, which increases the difficulty of microscopic characterization and analysis, making the microscopic interface of all-solid state batteries not yet clear.
Atomic-scale sample preparation and characterization of solid-state batteries are carried out using a completely air-isolated method. The specific steps include disassembling the all-solid-state battery in a glove box in an argon atmosphere, cryo-polishing and thinning through FIB-SEM double-beam electron microscopy, and then The samples were transported in liquid nitrogen to avoid air contact, and finally observed under a transmission electron microscope at -160°C.
It achieves true atomic scale characterization of all-solid-state batteries, avoids sample damage and analysis errors caused by air contact, and reveals the impact of the microstructure of electrode materials and electrolytes on macroscopic performance.
Smart Images

Figure CN119355020A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of all-solid-state battery characterization, and in particular relates to a characterization system, method and application of atomic-scale sample preparation of solid-state batteries that are completely isolated from air. Background Art
[0002] With the transformation of the global energy structure, all-solid-state batteries have rapidly emerged as a new generation of high-energy density batteries, and people's research on all-solid-state batteries has become more and more in-depth. However, unlike traditional liquid battery systems, the solid-solid contact of solid-state batteries also leads to interface problems that greatly affect the macroscopic electrochemical performance of all-solid-state batteries. At present, most of the processes such as interface material transport, interface electrochemistry, and interface evolution in all-solid-state batteries are based on mechanistic studies based on macroscopic analysis methods such as X-ray diffraction analysis, X-ray photoelectron spectroscopy analysis, and Raman spectroscopy analysis. In recent years, with the application of cryo-electron microscopy analysis, the veil of liquid batteries at the atomic scale has gradually been revealed. However, the electrolytes in solid-state batteries, especially sulfide electrolytes and halide electrolytes, are extremely sensitive to water. Due to the air stability and electron beam / ion beam sensitivity of all-solid-state batteries, there are various deficiencies in related sample preparation and characterization methods, which greatly increases the difficulty of characterizing and analyzing the microscopic scale of all-solid-state batteries, making the microscopic interface of all-solid-state batteries not yet clear.
[0003] Therefore, the development of transmission electron microscopy analysis of all-solid-state battery interfaces plays an extremely important role in revealing all-solid-state battery interface research, understanding the influence of electrode material-electrolyte microstructure on macroscopic performance, guiding the innovation of key materials, and leading the transformation of all-solid-state battery technology system. Summary of the invention
[0004] In response to the above technical problems, the present invention proposes a characterization system, method and application of atomic-scale sample preparation of solid-state batteries that are completely isolated from air. The specific characterization method is: the all-solid-state battery after operation is disassembled in a glove box filled with argon atmosphere, and after pre-preparation into samples to be processed, it enters the FIB by vacuum transmission. The freezing process at -160°C reduces the influence of the ion beam on the thin slice. When the ion beam processing is completed, the FIB thin slice is placed in liquid nitrogen by vacuum transmission to avoid the influence of air; the frozen transfer sample rod is filled with liquid nitrogen to ensure that it is cooled to the liquid nitrogen temperature, and then the FIB thin slice in the liquid nitrogen is transferred to the transmission electron microscope freezing rod. The entire transmission process ensures that the FIB thin slice is below the liquid nitrogen liquid level, thereby isolating the influence of air; finally, it enters the transmission electron microscope and collects data at -160°C. Therefore, the present invention is applicable to various all-solid-state battery systems, and provides an extremely important sample preparation and characterization method for revealing the effect of the microscopic interface of all-solid-state batteries on macroscopic performance.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention:
[0007] A completely air-isolated solid-state battery atomic-scale sample characterization system, including:
[0008] Solid-state battery processing unit, including an argon atmosphere glove box and a FIB-SEM dual-beam electron microscope;
[0009] The transmission unit comprises a flange, a transmission device and a cryo-transmission sample rod connected in sequence; wherein one end of the flange is connected to the FIB-SEM dual-beam electron microscope;
[0010] Characterization unit including transmission electron microscopy.
[0011] Preferably, the model of the FIB-SEM dual-beam electron microscope is Helios G4 cx.
[0012] Preferably, the transmission device is of model Zeptool Cryo-T.
[0013] The second technical solution of the present invention:
[0014] A characterization method for preparing a solid-state battery atomic scale sample completely isolated from air, wherein the following steps are performed according to the above characterization system:
[0015] (1) Disassembling the all-solid-state battery in a glove box with an argon atmosphere and preparing cross-sectional samples;
[0016] (2) transmitting the cross-section sample to a FIB-SEM double-beam electron microscope;
[0017] (3) extracting the solid electrode / solid electrolyte interface and performing cryo-polishing treatment by FIB, then thinning it at 30 kV voltage, using currents of 2.5 nA, 0.79 nA, and 0.23 nA, and finally blowing and removing the amorphous layer on the surface of the FIB slice with 8 kV / 68 pA and 5 kV / 41 pA, respectively, to obtain a FIB slice (sample preparation);
[0018] (4) Under an argon atmosphere, the FIB slice is sequentially transferred to a transmission electron microscope through a flange, a transfer device, and a cryotransfer sample rod for low-temperature observation.
[0019] Beneficial effect: During the sample preparation and characterization process, the present invention uses argon or liquid nitrogen protection throughout the process to avoid contact between the sample and the air, so that the real information of the sample can be finally obtained.
[0020] Preferably, the temperature during the freeze polishing process in step (3) and the low-temperature observation process in step (4) is both -160°C.
[0021] Preferably, the cryo-polishing treatment is performed at a low temperature of -160°C using a Ga ion beam at a voltage of 30 kV and a beam current of 9.3 nA.
[0022] Preferably, the transmission process in step (4) is carried out under argon atmosphere.
[0023] Preferably, the model of the cryotransfer sample rod is Fischione Model 2550.
[0024] Preferably, the temperature of the cryotransfer sample rod needs to be cooled to the temperature of liquid nitrogen.
[0025] Preferably, the transmission electron microscope is of model FEI-Titan G2.
[0026] The third technical solution of the present invention:
[0027] The application of the above-mentioned characterization system or method for atomic-scale sampling of solid-state batteries that are completely isolated from air in the microscopic analysis of the interface of all-solid-state batteries.
[0028] Preferably, the electrolyte of the all-solid-state battery is a sulfide electrolyte, a halide electrolyte, or an oxide electrolyte.
[0029] Preferably, the all-solid-state battery includes one or more of a Si / LPS / NMC all-solid-state battery, a Li / LPS / Li sulfide-based all-solid-state battery, a LiIn / LPS / NMC sulfide-based all-solid-state battery, a Li / LLZTO / Li oxide-based all-solid-state battery, and a Li / LZC / Li halide-based all-solid-state battery.
[0030] Compared with the prior art, the present invention has the following advantages and technical effects:
[0031] (1) The present invention protects the sample by using argon and liquid nitrogen protection during the sample preparation and transmission process, thereby avoiding contact between the sample and the air and obtaining true information of the all-solid-state battery;
[0032] (2) The temperature of the present invention is maintained at -160°C during the sample preparation and observation (photography), which reduces the damage of the ion beam and electron beam to the sample and characterizes the interface of the all-solid-state battery at the atomic scale;
[0033] (3) The present invention has a wide range of applications, covering the atomic-scale characterization of any interface of oxide, sulfide and halide-based all-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0035] Figure 1 It is a schematic diagram of the process flow of the whole process of sample transmission of the present invention;
[0036] Figure 2 a is the original all-solid-state battery sample in Example 1, and b is the SEM image of Example 1 after FIB polishing at a low temperature of -160°C using a Ga ion beam at a voltage of 30 kV and a beam current of 9.3 nA;
[0037] Figure 3 This is a FIB slice image of the all-solid-state battery processed in Example 1 of the present invention;
[0038] Figure 4 It is a TEM image of the all-solid-state battery FIB slice prepared in Examples 1-5 of the present invention. DETAILED DESCRIPTION
[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0040] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0044] like Figure 1 As shown, the present invention provides a characterization method for atomic scale sample preparation of solid-state batteries completely isolated from air, which specifically includes the following steps:
[0045] (1) A Helios G4 cx FIB-SEM dual-beam electron microscope was modified by adding a flange on one side of the electron microscope cabin and connecting the transmission device Zeptool Cryo-T through the flange to transmit the sample in an airtight manner;
[0046] (2) The all-solid-state battery is cryo-polished by FIB to obtain a FIB thin section that can be observed by TEM;
[0047] (3) sending the slice into liquid nitrogen through a transmission device;
[0048] (4) Cooling the Fischione Model 2550 cryotransfer sample holder to liquid nitrogen temperature;
[0049] (5) The thin slice in liquid nitrogen is isolated from air and transferred to the TEM cryotransfer sample holder, and then transferred into a FEI-Titan G2 transmission electron microscope at liquid nitrogen temperature;
[0050] (6) TEM observation was performed at liquid nitrogen temperature.
[0051] A completely air-isolated solid-state battery atomic-scale sample characterization system, including:
[0052] Solid-state battery processing unit, including an argon atmosphere glove box and a FIB-SEM dual-beam electron microscope;
[0053] The transmission unit comprises a flange, a transmission device and a cryo-transmission sample rod connected in sequence; wherein one end of the flange is connected to the FIB-SEM dual-beam electron microscope;
[0054] Characterization unit including transmission electron microscopy.
[0055] Preferably, the model of the FIB-SEM dual-beam electron microscope is Helios G4 cx.
[0056] Preferably, the transmission device is of model Zeptool Cryo-T.
[0057] The raw materials used in the present invention are all purchased from the market.
[0058] The technical solution of the present invention is further illustrated by the following embodiments.
[0059] Example 1
[0060] A characterization method for atomic-scale sample preparation of a solid-state battery completely isolated from air comprises the following steps:
[0061] (1) Run the Si / LPS / NMC all-solid-state battery through a charge and discharge tester (LAND CT2001A);
[0062] (2) Disassemble the Si / LPS / NMC all-solid-state battery in a glove box filled with argon atmosphere and prepare cross-sectional samples;
[0063] (3) Transfer the all-solid-state battery cross-section sample into the FEI-Helios G4 cx;
[0064] (4) The Si / LPS interface was extracted and FIB cryo-polished at -160°C using a Ga ion beam at 30 kV and 9.3 nA. Thinning was then performed at 30 kV with currents of 2.5 nA, 0.79 nA, and 0.23 nA. Finally, the amorphous layer on the surface of the FIB slice was removed by purging with 8 kV / 68 pA and 5 kV / 41 pA.
[0065] (5) The sample was isolated from air and transferred into a FEI-Titan G2 transmission electron microscope for cryo-observation at −160°C via a flange, a transfer device (Zeptool Cryo-T), and a Fischione Model 2550 cryo-transfer sample rod (filled with liquid nitrogen and kept cooled to liquid nitrogen temperature during the transfer process).
[0066] The TEM slices processed by FIB using the above method completely avoid air transmission. After entering the transmission electron microscope, no side reactions occur, revealing the microstructure of the real interface between the Si negative electrode and the LPS all-solid-state sulfide electrolyte.
[0067] Figure 2 This is the SEM image of the all-solid-state battery prepared in Example 1 of the present invention, wherein a is the original all-solid-state battery sample, and b is the SEM image after FIB cryo-polishing processing; it can be clearly seen from the figure that cracks are generated between the Si negative electrode and the electrolyte after the cycle, indicating that the solid-state battery operating under stack pressure cannot avoid the problems caused by volume expansion and contraction.
[0068] Figure 3 This is a FIB thin-section image of the all-solid-state battery prepared in Example 1 of the present invention; it can be seen from the figure that the Si negative electrode has an obvious interface layer with the electrolyte after cycling.
[0069] Figure 4 Figures a and b are TEM images of the all-solid-state battery prepared in Example 1 of the present invention, where a is a low-magnification TEM image and b is an atomic-scale HRTEM image. It can be seen from the figures that there is a nanocrystalline reaction layer mainly composed of Li2S between Si and the electrolyte.
[0070] Example 2
[0071] A characterization method for atomic-scale sample preparation of a solid-state battery completely isolated from air comprises the following steps:
[0072] (1) Run the Li / LPS / Li sulfide-based all-solid-state battery through a charge and discharge tester (LAND CT2001A);
[0073] (2) Disassemble the Li / LPS / Li all-solid-state battery in a glove box filled with argon atmosphere and prepare cross-sectional samples;
[0074] (3) Transfer the all-solid-state battery cross-section sample into the FEI-Helios G4 cx;
[0075] (4) The Li / LPS interface was extracted and FIB cryo-polished at -160°C using a Ga ion beam at 30 kV and 9.3 nA. Thinning was then performed at 30 kV with currents of 2.5 nA, 0.79 nA, and 0.23 nA. Finally, the amorphous layer on the surface of the FIB slice was removed by purging with 8 kV / 68 pA and 5 kV / 41 pA.
[0076] (5) The TEM slice was isolated from air and transferred into a FEI-Titan G2 transmission electron microscope for cryo-observation at −160°C via a flange, a transfer device (Zeptool Cryo-T), and a Fischione Model 2550 cryo-transfer sample rod (filled with liquid nitrogen and kept cooled to liquid nitrogen temperature during the transfer process).
[0077] The TEM slices processed by FIB using the above method completely avoid air transmission. After entering the transmission electron microscope, no side reactions occur, revealing the microstructure of the real interface between the Li negative electrode and the LPS sulfide solid electrolyte.
[0078] Figure 4Figures c and d are TEM images of the all-solid-state battery prepared in Example 2 of the present invention, where c is a low-magnification TEM image and d is an atomic-scale HRTEM image. It can be seen from the figures that there is a nanocrystalline reaction layer mainly composed of Li2S between Li and the electrolyte.
[0079] Example 3
[0080] A characterization method for atomic-scale sample preparation of a solid-state battery completely isolated from air comprises the following steps:
[0081] (1) Run the LiIn / LPS / NMC sulfide-based all-solid-state battery through a charge and discharge tester (LAND CT2001A);
[0082] (2) Disassemble the LiIn / LPS / NMC all-solid-state battery in a glove box filled with argon atmosphere and prepare cross-sectional samples;
[0083] (3) Transfer the all-solid-state battery cross-section sample into the FEI-Helios G4 cx;
[0084] (4) The LiIn / LPS interface was extracted and FIB cryo-polished at -160°C using a Ga ion beam at a voltage of 30 kV and a beam current of 9.3 nA; then thinning was performed at a voltage of 30 kV, using currents of 2.5 nA, 0.79 nA, and 0.23 nA, and finally the amorphous layer on the surface of the FIB slice was purged and removed using 8 kV / 68 pA and 5 kV / 41 pA, respectively;
[0085] (5) The TEM slice was isolated from air and transferred into a FEI-Titan G2 transmission electron microscope for cryo-observation at −160°C via a flange, a transfer device (Zeptool Cryo-T), and a Fischione Model 2550 cryo-transfer sample rod (filled with liquid nitrogen and kept cooled to liquid nitrogen temperature during the transfer process).
[0086] The TEM slices processed by FIB using the above method completely avoid air transmission. After entering the transmission electron microscope, no side reactions occur, revealing the microstructure of the real interface between the LiIn negative electrode and the LPS sulfide solid electrolyte.
[0087] Figure 4 Figures e and f are TEM images of the all-solid-state battery prepared in Example 3 of the present invention, where e is a low-magnification TEM image and f is an atomic-scale HRTEM image. It can be seen from the figures that there is a nanocrystalline reaction layer mainly composed of Li2S between LiIn and the electrolyte.
[0088] Example 4
[0089] A characterization method for atomic-scale sample preparation of a solid-state battery completely isolated from air comprises the following steps:
[0090] (1) Run the Li / LLZTO / Li oxide-based all-solid-state battery through a charge and discharge tester (LAND CT2001A);
[0091] (2) Disassemble the Li / LLZTO / Li all-solid-state battery in a glove box filled with argon atmosphere and prepare cross-sectional samples;
[0092] (3) Transfer the all-solid-state battery cross-section sample into the FEI-Helios G4 cx;
[0093] (4) The Li / LLZTO interface was extracted and FIB cryo-polished at -160°C using a Ga ion beam at a voltage of 30 kV and a beam current of 9.3 nA; then thinning was performed at a voltage of 30 kV, using currents of 2.5 nA, 0.79 nA, and 0.23 nA, and finally the amorphous layer on the surface of the FIB slice was purged and removed using 8 kV / 68 pA and 5 kV / 41 pA, respectively;
[0094] (5) The TEM slice was isolated from air and transferred into a FEI-Titan G2 transmission electron microscope for cryo-observation at −160°C via a flange, a transfer device (Zeptool Cryo-T), and a Fischione Model 2550 cryo-transfer sample rod (filled with liquid nitrogen and kept cooled to liquid nitrogen temperature during the transfer process).
[0095] The TEM slices processed by FIB using the above method completely avoid air transmission. After entering the transmission electron microscope, no side reactions occur, revealing the microstructure of the real interface between the Li negative electrode and the LLZTO oxide solid electrolyte.
[0096] Figure 4 Figures g and h are TEM images of the all-solid-state battery prepared in Example 4 of the present invention, where g is a low-magnification TEM image and h is an atomic-scale HRTEM image. It can be seen from the figures that there is an interface layer of Li2CO3 between Li and the electrolyte.
[0097] Example 5
[0098] A characterization method for atomic-scale sample preparation of a solid-state battery completely isolated from air comprises the following steps:
[0099] (1) Run Li / LZC / Li halide-based all-solid-state batteries through a charge and discharge tester (LAND CT2001A);
[0100] (2) Disassemble the Li / LZC / Li all-solid-state battery in a glove box filled with argon atmosphere and prepare cross-sectional samples;
[0101] (3) Transfer the all-solid-state battery cross-section sample into the FEI-Helios G4 cx;
[0102] (4) The Li / LZC interface was extracted and FIB cryo-polished at -160°C using a Ga ion beam at 30 kV and 9.3 nA. Thinning was then performed at 30 kV with currents of 2.5 nA, 0.79 nA, and 0.23 nA. Finally, the amorphous layer on the surface of the FIB slice was removed by purging with 8 kV / 68 pA and 5 kV / 41 pA.
[0103] (5) The TEM slice was isolated from air and transferred into a FEI-Titan G2 transmission electron microscope for cryo-observation at −160°C via a flange, a transfer device (Zeptool Cryo-T), and a Fischione Model 2550 cryo-transfer sample rod (filled with liquid nitrogen and kept cooled to liquid nitrogen temperature during the transfer process).
[0104] The TEM slices processed by FIB using the above method completely avoid air transmission. After entering the transmission electron microscope, no side reactions occur, revealing the microstructure of the real interface between the Li negative electrode and the LZC halide solid electrolyte.
[0105] Figure 4 In the figure, i and j are TEM images of the all-solid-state battery prepared in Example 5 of the present invention, wherein i is a low-magnification TEM image and j is an atomic-scale HRTEM image. It can be seen from the figure that there is an interface layer of LiCl between Li and the electrolyte.
[0106] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A solid-state battery atomic scale sample characterization system completely isolated from air, characterized in that: include: Solid-state battery processing unit, including a glove box filled with argon atmosphere and a FIB-SEM dual-beam electron microscope; The transmission unit comprises a flange, a transmission device and a cryo-transmission sample rod connected in sequence; wherein one end of the flange is connected to the FIB-SEM dual-beam electron microscope; Characterization unit including transmission electron microscopy.
2. The characterization system for atomic scale sample preparation of solid-state batteries completely isolated from air according to claim 1, characterized in that: The model of the FIB-SEM dual-beam electron microscope is Helios G4 cx.
3. The characterization system for atomic scale sample preparation of solid-state batteries completely isolated from air according to claim 1, characterized in that: The model of the transmission device is Zeptool Cryo-T.
4. A method for characterizing atomic-scale samples of solid-state batteries that are completely isolated from air, characterized in that: The characterization system according to any one of claims 1 to 3 performs the following steps: (1) Disassembling the all-solid-state battery in a glove box filled with argon atmosphere and preparing cross-sectional samples; (2) transmitting the cross-section sample to a FIB-SEM double-beam electron microscope; (3) extracting the solid electrode / solid electrolyte interface and performing cryo-polishing by FIB to obtain FIB thin sections; (4) Under an argon atmosphere, the FIB slice is sequentially transferred to a transmission electron microscope through a flange, a transfer device, and a cryotransfer sample rod for low-temperature observation.
5. The characterization method for atomic scale sample preparation of a solid-state battery completely isolated from air according to claim 4, characterized in that: The temperature during the freeze polishing process in step (3) and the low-temperature observation process in step (4) is both -160°C.
6. The method for characterizing atomic-scale samples of solid-state batteries completely isolated from air according to claim 4, characterized in that: The cryotransfer sample holder is filled with liquid nitrogen, and the cryotransfer sample holder is cooled to the temperature of liquid nitrogen during the transfer process.
7. The characterization method for atomic scale sample preparation of a solid-state battery completely isolated from air according to claim 6, characterized in that: The model of the cryotransfer sample holder is Fischione Model 2550.
8. Application of the characterization system according to any one of claims 1 to 3 or the characterization method according to any one of claims 4 to 7 in microscopic analysis of all-solid-state battery interfaces.
9. The use according to claim 8, characterized in that: The electrolyte of the all-solid-state battery is a sulfide electrolyte, a halide electrolyte or an oxide electrolyte.
10. The use according to claim 8, characterized in that: The all-solid-state battery includes one or more of a Si / LPS / NMC all-solid-state battery, a Li / LPS / Li sulfide-based all-solid-state battery, a LiIn / LPS / NMC sulfide-based all-solid-state battery, a Li / LLZTO / Li oxide-based all-solid-state battery or a Li / LZC / Li halide-based all-solid-state battery.